Application of bokashi and sunn hemp (Crotalaria juncea L.) to improve inorganic fertilizer efficiency on maize (Zea mays L.) - Yuliana, A I; Sumarni, T; Islami, T (Brawijaya University, 2015)
A field experiment was conducted lo learn about the effect of Bokashi and Sunn hemp (Crotalaria junceaL.)on maize production and inorganic fertilizer use efficiency on maize. The experiment was conducted in Jatikerto, Malang; at the altitude of 303 m above sea level, in Alfisol soil type, the average daily temperature ranges 21-33oC, from Juneto October 2013. The experiment was conducted as factorial, designed in a randomized block design (RBD). The first factor was dose ofinorganic fertilizer (100% ; 75% and50% of recommendation dose). The second factor was the organic fertilizer(Without organic fertilizer20 tBokashi/ ha, 20 t Sunn hemp/ha, 10 t Bokashi/ha + 10 t Sunn hemp/ha). The results showed that application of 20 t Bokashi/ha, 20 t Sunn hemp/ha, and combination of 10 t Bokashi/ha + 10 t Sunn hemp/ha, along with the application of inorganic fertilizer by dose of 100% increased the yields of maize for about 41.8%; 47.6% and 54.7% (10.73 t/ha; 11.17 t/ha, and 11.71 t/ha), respectively. The yield and nutrient use efficiency in the treatment dose of 100% inorganic fertilizer did not have any significant difference from the application of 20 t Bokashi /ha, 20 t Sunn hemp/ha, and 10 t Bokashi/ha + 10 t Sunn hemp/ha along with doses of inorganic fertilization 75% and 50%. Therefore, the organic fertilizer of 20 t Bokashi/ ha, 20 t Sunn hemp/ha, and combination of 10 t Bokashi/ha+ 10 t Sunn hemp/ha could reduce the need of inorganic fertilizer for about 50%.Â